The Role of the Internet and Social Media in the Spread of ISIS in Indonesia - Permana, Indra Martian; Adam, Fadzli (Halaqa: Islamic Education Journal, 2021)
The Islamic State of Iraq and Syria (ISIS) is an organization against the background of Islamic jihad which was founded in Syria in 2014 and then brought the terror movement into war against those who disagreed with their movements including fighting Muslims in Syria. The advancement of Information Technology which gave birth to the internet and social media turned out to benefit ISIS, by spreading, recruiting, and raising funds through the internet and social media. ISIS distribution and propaganda can enter Indonesia through the internet and social media through the emergence of ISIS sites, Facebook ISIS and online bulletins and e-books online. The impact is that not a few Indonesian citizens are interested and join ISIS and even go to Syria and fight with ISIS.